2014
DOI: 10.1177/1460458213491512
|View full text |Cite
|
Sign up to set email alerts
|

Using advanced mobile devices in nursing practice – the views of nurses and nursing students

Abstract: Advanced mobile devices allow registered nurses and nursing students to keep up-to-date with expanding health-related knowledge but are rarely used in nursing in Sweden. This study aims at describing registered nurses' and nursing students' views regarding the use of advanced mobile devices in nursing practice. A cross-sectional study was completed in 2012; a total of 398 participants replied to a questionnaire, and descriptive statistics were applied. Results showed that the majority of the participants regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 26 publications
2
73
1
4
Order By: Relevance
“…One concern was whether mobile device use would negatively affect their performance [16]. Many expressed fears that patients would assume they were playing games or using devices for personal use [2]. Nurses were also cognizant of potential distractions that mobile devices offer in the provision of patient-centered care [1,2,16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…One concern was whether mobile device use would negatively affect their performance [16]. Many expressed fears that patients would assume they were playing games or using devices for personal use [2]. Nurses were also cognizant of potential distractions that mobile devices offer in the provision of patient-centered care [1,2,16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A 2013 study of American nurse leaders reported that although a growing number of nurses owned smartphones or tablets, these devices are rarely used in the practice of caring for patients [1]. Johansson reports in 2012 that compared to earlier studies nurses were increasingly using mobile technology in their practice but desktop computers and even paper-based guidelines were still widely used [2]. From a survey of a NHS Trust institution in London, England during 2015, Mobasheri reports that a growing number of doctors and nurses own and are using mobile devises with medical apps in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] According to some nurses who work in acute care and long-term care facilities, community settings, primary care programs and rural practice settings, using mobile devices in their practice setting has enhanced their skills and awareness of research evidence which has assisted them in their clinical practice. [10,11] Still other nurses who use mobile devices report spending less time completing unnecessary paperwork [12] which increases patient safety [13] including during blood product administration. [14,15] Mobile technologies have also influenced undergraduate nursing students' learning experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This technological boom runs alongside advances in 'smart technology' whereby different technologies and devices can 'talk to each other', allowing for the creation of care environments that not only monitor the safety and wellbeing of the client but respond to their changing needs in 'real time', for example, creating safe environments for people living with dementia (Bowes et al 2013). Despite these advices, there is evidence to suggest that such technologies remain underutilised and disliked in mental health practice (Johansson et al 2014). There would seem to be a number of reasons for this, none more so than the way that ICTs were first introduced and promoted in clinical practice.…”
mentioning
confidence: 99%